2011
DOI: 10.2217/pgs.11.40
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the LEP , LEPR and HTR2C Gene: Obesity and BMI Change in Patients Using Antipsychotic Medication in a Naturalistic Setting

Abstract: The LEPR Q223R polymorphism may be a risk factor for obesity in women with a psychotic disorder treated with atypical antipsychotic drugs. This is in line with earlier findings of our group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
2
19
0
2
Order By: Relevance
“…Several studies included in our results have replicated the association of -759C/T with AIWG [42,43,44,45,46], though negative and contradictory results were also reported [47,48,49,50,51,52,53,54]. One study involving a heterogeneous psychiatric sample reported that carriers of the HTR2C -759T allele were protected against the weight-inducing effects of olanzapine [42].…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Several studies included in our results have replicated the association of -759C/T with AIWG [42,43,44,45,46], though negative and contradictory results were also reported [47,48,49,50,51,52,53,54]. One study involving a heterogeneous psychiatric sample reported that carriers of the HTR2C -759T allele were protected against the weight-inducing effects of olanzapine [42].…”
Section: Resultsmentioning
confidence: 53%
“…Taken together, there is a sound theoretical basis supporting the potential involvement of LEP and LEPR in AP-induced metabolic dysregulation. Indeed, several studies from our review have implicated these genes in metabolic AAEs [46,52,72,73,74,75]. Still, negative and contradictory results have also been reported [44,62,76,77].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…По данным отдель-ных авторов, аллельные варианты AA гена LEP 2548 G/A ассоциированы с набором веса [80][81][82]. В то же время вышли публикации, указывающие на отсутствие взаимосвязи межу ОНП 2548G/A гена LEP и метаболическими нарушениями [83]. Несмотря на предполагаемое важное значение нейропетида Y в механизме регуляции пищевого поведения, достоверных исследований, показы-вающих влияние полиморфности генов данного фактора не так много.…”
unclassified